Caregivers of children with diabetes mellitus: challenges of caring for and perceptions of consultations in a South African public sector context - B. L. Dhada; D. R. Blackbeard (South African Family Practice)
Background: Understanding caregivers’ challenges in caring for children with diabetes mellitus (DM) and their perceptions of consultations with the multidisciplinary team (MDT) may be valuable in assisting in achieving control. Methods: Using a qualitative descriptive design, anonymised, transcribed recorded data from semi-structured interviews with a purposive sample of caregivers were thematically analysed in three areas: (a) challenges experienced in caring for their child, (b) feelings around MDT consultations pertaining to helpfulness, support and diabetes education, and (c) suggestions for clinic improvement. University of KwaZulu-Natal ethics committee approval and informed consent were obtained. Results: All caregivers (n = 14) were female with a mean age of 38 years. Total diabetes caring experience was 47.4 years. The primary caregiver was the mother in nine interviews. Ten interviewees were unemployed. The children’s ages ranged from 3 to 15 years with mean age at diagnosis of 6.7 years. Caregivers’ challenges in caring were reflected in two global themes: ‘DM care is difficult’ and needs a ‘process of adjustment’ over time to accept and meet demands. These included emotional, practical, financial, behavioural and social challenges. Caregivers’ feelings regarding overall consultations were mostly positive, including satisfaction. The MDT’s helpfulness and support were perceived as patient-centred and meeting education and care needs. Negative feelings were frustration and boredom. Clinic improvement suggestions included shorter waiting times and seeing the same doctor for continuity of care. Conclusion: Caregivers in South Africa experienced caring for children with DM as difficult, requiring an adjustment process. Perceptions of consultations were mostly positive. Relevant clinic improvements were suggested.